PENINGKATAN HASIL BELAJAR PPKn TENTANG POLITIK LUAR NEGERI BEBAS AKTIF DENGAN METODE BRAINSTORMING - Sumarwoto Sumarwoto (LPPM UNISDA, 2021)
The learning process is always gradual, starting from learning through signals, then through stimulus-response, chaining, learning verbally, learning to differentiate, learning concepts, to learning principles and principles. learn for problem solving. The result is capabilities, whether in the form of certain knowledge, attitudes, or skills. PPKn lessons are one of the lessons whose material continues to develop over time. The learning material requires the ability to analyze, generalize and the ability to remember, so it is often taught by some students. Based on the results of preliminary observations and interviews with PPKn subject teachers in class IX-A of SMPN 1 Pule Trenggalek, information was obtained that the average value of PPKn learning outcomes only reached an average of 54.2, specifically foreign policy material is free and active and this has not meet the learning completeness criteria set at 69 (KKM). There were only 10 students who scored ≥ 69 or 36.7% and 20 students or 64.3% had not reached the KKM. So through this classroom action research, the researcher will apply the brainstorming learning method. The subjects of this study were students of class IX-A at SMPN 1 Pule Trenggalek in the 2019/2020 academic year with 30 students. From the results of the learning activities that have been carried out for two cycles, and based on all the discussions and analyzes that have been carried out, it can be concluded that the application of the brainstorming method can improve student learning achievement on PPKn material on free and active foreign policy. This is based on the post test score which continues to increase from the first to the second cycle. The application of the brainstorming method in PPKn learning about free and active foreign policy, begins with giving group assignments. Each group was assigned the task of discussing free and active foreign policy. In advanced learning, students complete assignments independently.